Expression Analysis of Gnrh1 and Gnrhr1 in Spermatogenic Cells of Rat - Vincenza Ciaramella; Rosanna Chianese; Paolo Pariante; Silvia Fasano; Riccardo Pierantoni; Rosaria Meccariello (International Journal of Endocrinology)
Hypothalamic Gonadotropin Releasing Hormone (GnRH), via GnRH receptor (GnRHR), is the main actor in the control of reproduction, in that it induces the biosynthesis and the release of pituitary gonadotropins, which in turn promote steroidogenesis and gametogenesis in both sexes. Extrabrain functions of GnRH have been extensively described in the past decades and, in males, local GnRH activity promotes the progression of spermatogenesis and sperm functions at several levels. The canonical localization of Gnrh1 and Gnrhr1 mRNA is Sertoli and Leydig cells, respectively, but ligand and receptor are also expressed in germ cells. Here, we analysed the expression rate of Gnrh1 and Gnrhr1 in rat testis (180 days old) by quantitative real-time PCR (qPCR) and by in situ hybridization we localized Gnrh1 and Gnrhr1 mRNA in different spermatogenic cells of adult animals. Our data confirm the testicular expression of Gnrh1 and of Gnrhr1 in somatic cells and provide evidence that their expression in the germinal compartment is restricted to haploid cells. In addition, not only Sertoli cells connected to spermatids in the last steps of maturation but also Leydig and peritubular myoid cells express Gnrh1.